ISOLASI DAN IDENTIFIKASI JAMUR SELULOLITIK PADA LIMBAH PRODUKSI BIOETANOL DARI SINGKONG YANG BERPOTENSI DALAM PENGOLAHAN LIMBAH MENJADI PAKAN DOMBA - Yani Suryani; Poniah Andayaningsih; Iman Hernaman (JURNAL ISTEK, 2012)
In the bioethanol production process of waste generated that is equal to 90% of the fermentation solution. With the vast amount of waste is the waste treatment process becomes very important, one of which is to process into livestock woof. The solid bioethanol waste containing cyanide (HCN) 5.8177 mg/kg, water 95.21%, ash 0.39%, protein 8.16%, crude fiber 5.45%, crude fat 2.06%, and carbohydrates 83,94%. The processing solid bioethanol waste into livestock woof can be done by utilizing the existing fungi on solid bioethanol waste. Crude fiber (cellulose) and carbohydrates are a source of cellulolytic fungal. Cellulolytic fungi can degrade the role of organic materials contained in solid into bioethanol waste so that the source of highly nutritious livestock woof. This study aims to determine the types of mold and fungi cellulolytic isolates contained in solid bioethanol waste the potentially in processing bioethanol waste into livestock woof. The research was conducted using the descriptive analysis method. The medium used for culturing the fungus and isolate the medium Potato Dextrose Agar (PDA). Fungal isolation conducted by using dilution series and pour plate method and identification with the Moist Chamber method. To find out cellulolytic fungi using selective medium Carboxy Methyl Cellulose (CMC) and identification of fungi made to genus level based on macroscopic and microscopic characterization. In this study obtained 10 isolates of the fungus from the genus Aspergillus sp 1, Aspergillus sp 2, Aspergillus sp 3, Aspergillus niger, Cladosporium sp, Mucor sp, Penicillium sp 1, Penicillium sp 2, Rhizopus sp and Trichoderma viride. The results of cellulase enzyme activity assay showed that 9 from 10 isolates of the fungus has the capability of cellulose degradation. Isolates that largest produce the enzyme cellulase is Trichoderma viride, Penicillium sp 1, Cladosporium spand Aspergillus niger.